More Than 2% of Circulating Tumor Plasma Cells Defines Plasma Cell Leukemia–Like Multiple Myeloma. Issue 7 (1st March 2023) - Jelinek, Tomas; Bezdekova, Renata; Zihala, David; Sevcikova, Tereza; Anilkumar Sithara, Anjana; Pospisilova, Lenka; Sevcikova, Sabina; Polackova, Petra; Stork, Martin; Knechtova, Zdenka; Venglar, Ondrej; Kapustova, Veronika; et al.
Abstract : PURPOSE: Primary plasma cell leukemia (PCL) is the most aggressive monoclonal gammopathy. It was formerly characterized by ≥ 20% circulating plasma cells (CTCs) until 2021, when this threshold was decreased to ≥ 5%. We hypothesized that primary PCL is not a separate clinical entity, but rather that it represents ultra-high-risk multiple myeloma (MM) characterized by elevated CTC levels. METHODS: We assessed the levels of CTCs by multiparameter flow cytometry in 395 patients with newly diagnosed transplant-ineligible MM to establish a cutoff for CTCs that identifies the patients with ultra-high-risk PCL-like MM. We tested the cutoff on 185 transplant-eligible patients with MM and further validated on an independent cohort of 280 transplant-ineligible patients treated in the GEM-CLARIDEX trial. The largest published real-world cohort of patients with primary PCL was used for comparison of survival. Finally, we challenged the current 5% threshold for primary PCL diagnosis. RESULTS: Newly diagnosed transplant-ineligible patients with MM with 2%-20% CTCs had significantly shorter progression-free survival (3.1 v 15.6 months; P < .001) and overall survival (14.6 v 33.6 months; P = .023) than patients with < 2%. The 2% cutoff proved to be applicable also in transplant-eligible patients with MM and was successfully validated on an independent cohort of patients from the GEM-CLARIDEX trial. Most importantly, patients with 2%-20% CTCs had comparable dismal outcomes with primary PCL. Moreover, after revealing a low mean difference between flow cytometric and morphologic evaluation of CTCs, we showed that patients with 2%-5% CTCs have similar outcomes as those with 5%-20% CTCs. CONCLUSION: Our study uncovers that ≥ 2% CTCs is a biomarker of hidden primary PCL and supports the assessment of CTCs by flow cytometry during the diagnostic workup of MM.